Actinic keratosis: comprehensive review of current treatments and emerging therapeutic innovations - Ceryn, Justyna; Lesiak, Aleksandra; Sobolewska-Sztychny, Dorota; Noweta, Marcin; Ciążyńska, Magdalena; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Actinic keratosis (AK) is a prevalent benign intraepidermal dysplasia, classified as squamous cell carcinoma in situ (SCC in situ ). Chronic ultraviolet (UV) light exposure is the primary etiological factor for AK, which predominantly manifests in sun-exposed areas. Management of AK emphasizes primary prevention through education, sun protection, and vigilant patient monitoring. Therapeutic strategies for AK are categorized into lesion-directed and field-directed approaches, encompassing topical treatments (imiquimod, 5-fluorouracil, diclofenac) and physical modalities (cryotherapy, photodynamic therapy, chemical peels, laser therapy, electrocoagulation, curettage). This comprehensive review discusses the current treatments and explores novel therapeutic options for AK.